2017
DOI: 10.3390/ijms18081652
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling in Human Diseases: New Advances and Perspectives

Abstract: In the last decades, transcriptome profiling has been one of the most utilized approaches to investigate human diseases at the molecular level. Through expression studies, many molecular biomarkers and therapeutic targets have been found for several human pathologies. This number is continuously increasing thanks to total RNA sequencing. Indeed, this new technology has completely revolutionized transcriptome analysis allowing the quantification of gene expression levels and allele-specific expression in a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
153
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(169 citation statements)
references
References 102 publications
(143 reference statements)
0
153
0
7
Order By: Relevance
“…[31] [26]. To our knowledge, this study is the first example of the use of RT-dPCR for absolute quantification of transcriptomic signatures in infectious diseases, as anticipated by review articles [32]. Previous studies showed that RT-dPCR has a high accuracy for assessing absolute quantification of RNA and did not show significant inter-assay agreement [22].…”
Section: Discussionmentioning
confidence: 87%
“…[31] [26]. To our knowledge, this study is the first example of the use of RT-dPCR for absolute quantification of transcriptomic signatures in infectious diseases, as anticipated by review articles [32]. Previous studies showed that RT-dPCR has a high accuracy for assessing absolute quantification of RNA and did not show significant inter-assay agreement [22].…”
Section: Discussionmentioning
confidence: 87%
“…Transcriptomics studies entire sets of RNA transcripts in a particular context. Sample collection is critical; standardized collection tubes (eg PAXgene) can stabilize RNA for transport and storage.…”
Section: Resultsmentioning
confidence: 99%
“…At expressed loci, the difference between DNA-and RNAallele counts is driven by two major mechanisms -allele-preferential expression and RNA-editing. By using RNA-allele counts, ReQTLs are readily applicable to study both of the above mechanisms and to help elucidate their increasingly recognized role in diverse cellular processes (Imprialou et al, 2017;Casamassimi et al, 2017;Do et al, 2017;Eisenberg and Erez Y Levanon, 2018;Gagnidze et al, 2018;Moreno-Moral et al, 2017;Vandiedonck, 2018). Furthermore, compared to DNA-allele count, correlation of variant RNAallele frequency with gene expression holds several technical advantages.…”
Section: Discussionmentioning
confidence: 99%